Systematic review with meta‐analysis: self‐expanding metal stents in patients with cirrhosis and severe or refractory oesophageal variceal bleeding. Issue 11 (16th October 2015) - Marot, A.; Trépo, E.; Doerig, C.; Moreno, C.; Moradpour, D.; Deltenre, P.
Summary: Background: The prognosis of patients with cirrhosis and acute variceal bleeding is very poor when the standard‐of‐care fails to control bleeding. New treatment modalities are needed in these patients. Aim: To synthesise the available evidence on the efficacy of self‐expanding metal stents (SEMS) in patients with cirrhosis and severe or refractory oesophageal variceal bleeding. Methods: Meta‐analysis of trials evaluating SEMS in patients with cirrhosis and severe or refractory oesophageal variceal bleeding. Results: Thirteen studies were included. The pooled estimate rates were 0.40 (95% confidence interval, CI = 0.31–0.49) for death, 0.41 (95% CI = 0.29–0.53) for liver‐related death and 0.36 (95% CI = 0.26–0.47) for death at day 30, with low heterogeneity between studies. The pooled estimate rates were 0.12 (95% CI = 0.07–0.21) for mortality related to variceal bleeding, and 0.18 (95% CI = 0.11–0.29) for failure to control bleeding with SEMS, with no or low heterogeneity between studies. The pooled estimate rate were 0.16 (95% CI = 0.04–0.48) for rebleeding after stent removal and 0.28 (95% CI = 0.17–0.43) for stent migration, with high heterogeneity. A significant proportion of patients had access to liver transplantation or to TIPSS [pooled estimate rate 0.10 (95% CI = 0.04–0.21) and 0.26 (95% CI = 0.18–0.36), respectively]. Conclusions: Fewer than 40% of patients treated with SEMS were dead at 1 month. SEMS can be used as a bridge to TIPSS or to liver transplantation in a significant proportion of patients. Additional studies are required to identify potential risk factors leading to a poor prognosis in patients with acute variceal bleeding in whom the use of SEMS could be considered.